Evaluating potentials of passive solar heating renovation for the energy poverty alleviation of plateau areas in developing countries: A case study in rural Qinghai-Tibet Plateau, China. (15th July 2019) - Liu, Zhijian; Wu, Di; He, Bao-Jie; Wang, Qiaomei; Yu, Hancheng; Ma, Wensheng; Jin, Guangya
Highlights: Effect of passive heating renovation on energy poverty alleviation was verified. Coal consumption and thermal comfort were measured and compared respectively. Air tightness, thermal defect and indoor air quality were measured and evaluated. Potential of the passive heating renovation was explored and further optimized. Affiliated issues for alleviating energy poverty in policy, technology, etc. were discussed. Abstract: Energy poverty refers to a situation that people cannot access and use energy safely. It is a major challenge for the global energy system because of its negative impacts on household income, health, education, gender equality and environmental conditions. To solve this problem, many countries advocate the development and promotion of passive solar technology, but the effectiveness of them for energy poverty mitigation has not been evidenced. Therefore, based on empirical studies in the rural areas of Qinghai-Tibet Plateau, this paper aims at investigating the effectiveness of passive solar heating renovation to alleviate energy poverty in rural plateau areas. Specifically, this paper compared and analyzed the coal consumption and indoor air quality during the heating period before and after the renovation of a single-storey building. Further, based on the IES-VE numerical simulation, this paper analyzed the impact of building envelope structure performance on indoor air temperature. The results show that after building renovation, the coal consumption during the heating period could be reduced by 97 kg/week, while the indoor average temperature of two bedrooms were increased by 4.8 °C and 1.7 °C respectively. Setting up the coal stove as an auxiliary heating device, can alleviate the defects of insufficient heating of passive solar energy technology, and indoor temperature could be further improved. However, indoor air quality was lowered because of the high PM2.5 concentration. In contrast, improving envelope performance could further improve the average temperature of two bedrooms and the sunspace to 16.7 °C, 15.9 °C and 15.6 °C, meeting the requirements of indoor space heating. In general, passive solar heating could achieve satisfactory results, but to alleviate energy poverty effectively in rural plateau areas, further attention should be paid to other technical, economic, social and policy issues.